Crime of the KLA: shelling serbian market in the village Bresje - Đokić, Bojan D. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
After completion of the NATO aggression on Yugoslavia started much suffering of the Serbian and other minority communities in Kosovo and Metohija. Members of the Albanian paramilitary formations were escorted planning organized violence and terror, and for ethnic cleansing and destruction of the Serbian people in this region. The agreement that was signed between KFOR and the so-called KLA "The agreement K + 90" enabled the KLA carried out violence and terror against minority populations. One of the crimes that have taken place after the so-called the demilitarization of the KLA was an attack with explosives on the Serbian market in the village Bresje 28 September 1999. The crime was ethnically motivated to intimidate, pressure and the like oppression and ethnic cleansing of the Serbian population in Kosovo and Metohija. On the Serbian market in the village Bresje, where there were several hundred civilians were fired two grenades.This crime has produced three deaths and several dozen persons were injured. KFOR soon arrived at the scene and the injured persons drove in the Russian hospital in Kosovo Polje. The attack is the intention of the Albanian paramilitaries to kill large numbers of civilians of Serbian nationality, which would produce feelings of fear, anxiety, insecurity and inequality, and led to the displacement of a large number of people. When it comes to Serbian victims in Kosovo and Metohija justice remains blind, and so for this crime no one has been prosecuted. For the investigation of the crime was in charge of UNMIK police, with the assistance of KFOR. Immediately after the shelling of the market, were arrested two ethnic Albanians who were suspected of a crime, but were soon freed from detention. It is interesting also that this crime had expected, because the earlier sent anonymous reports of a possible attack, but that KFOR and UNMIK have failed to prevent his execution. Fear that appeared among the Serbian population in Bresje led to barricades. After the attack, the Italian KFOR troops are responsible for security of the Serbian population in Kosovo Polje, because the Serbs no longer had confidence in British KFOR troops. One of the reasons for shelling the market place was also intended to prevent the creation of a large Serbian enclave in Kosovo Polje and the surrounding area and that the Serb population from such a region displace. Consequences of shelling the market place are numerous: loss of 3 lives, wounding about 40 people, to cancel the agreement on the integration of Serbian and Albanian municipal authorities in Kosovo Polje, a sense of fear, inequality, insecurity and anxiety among the Serbian population, but also better protection of the Serbian population in Kosovo Polje and the environment.